Amphibole record of 1964 plinian and following dome-forming eruptions of Shiveluch volcano, Kamchatka - Gorbach N.V.; Philosofova T.M; Portnyagin M.V. (My University, 2020)
Shiveluch is one of the most active explosive volcanoes worldwide. During the last рlinian eruption in 1964 and the following (1980-current time) dome-forming eruptions Shiveluch has produced andesites and dacites (SiO2~60-64 wt.%) containing variably zoned, compositionally and texturally diverse amphibole phenocrysts. In this work, we attempt to decode the complex zoning of the amphibole crystals in the 55-year series of pumice, dome rocks and mafic enclaves in order to reconstruct the most recent evolution of the volcano plumbing system. The amphibole zoning in Shiveluch andesites reveals correlation with the style and date of eruption. High-Al cores mantled by low-Al rims in amphiboles from the 1964 plinian eruption record a drastic decrease of pressure and rapid magma ascent from the lower crust to the shallow magma chamber. Typically unzoned and often opacitized low-Al crystals from the early dome-building episodes in 1980-1981 and 1993-1995 reflect magma crystallization in the shallow magma chamber. Complexly zoned amphiboles from andesites erupted in 2000s indicate replenishment of the shallow magma chamber with mafic magma and syn-eruptive mixing processes. Amphibole-based barometric calculations obtained by different approaches indicate that the Shiveluch plumbing system is complex and comprises two, mafic and silicic magma storage zones at ~15-20 km and ~5-6 km depths. We suggest that both episodes of the plinian eruption in 1964 and the extensive dome growth in 2001-2016 were driven by influx of mafic magma in the shallow storage zone beneath Shiveluch. The mafic replenishment likely preceded the 1964 plinian eruption and repeatedly occurred during the period of extensive dome growth in 2001-2016. The variable styles of the recent Shiveluch eruptions may be controlled by the relative volume of the mafic recharges and their thermal and viscosity effects on the efficiency of magma mixing.
Keywords: 38.37.25 Вулканология; Шивелуч